Integrated of Pore Water Pressure, Hydraulic Gradient and Time Lag for Early Warning System at Sindang Heula Dam - Patra, Fadel Muhammad; Suharyanto; Sukamta (Kadiri University, 2025)
Excessive pore water pressure (PWP) is a primary factor contributing to internal erosion and catastrophic failures in embankment dams, accounting for nearly 40% of dam-related incidents worldwide. Despite routine monitoring, current practices remain limited by the absence of integrated analytical frameworks that simultaneously evaluate multiple hydraulic parameters for early warning system. This study aims to design an early warning system based on PWP, hydraulic gradient, and time lag parameters. The research was conducted at Sindang Heula Dam with 1,696 daily observation data (2020–2025) from four upstream and four downstream piezometers. Linear regression analysis was employed to predict PWP at low (86.613 masl), normal (106.613 masl), and maximum (108.613 masl) reservoir water level (RWL) conditions. Hydraulic gradients were derived from upstream–downstream head differentials, while time lags were determined based on the delay between peak reservoir levels and corresponding piezometric responses. The results revealed that upstream piezometers exhibited rapid responses (7–14 days) with strong correlations RWL (R² = 0.71–0.81), while downstream piezometers show delayed responses (35–42 days) with weaker correlation RWL (R² = 0.31–0.44). Hydraulic gradients increased from 0.32 at low to 0.63 at maximum RWL, indicating intensified seepage potential. The proposed integrated framework introduces a three-tier (green–yellow–red) early warning system based on real-time RWL thresholds, thereby improving proactive risk mitigation and strengthening dam safety management.